2022
DOI: 10.1109/tnsre.2022.3166824
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Patients With First-Episode Depression in the Eyes-Open and Eyes-Closed Conditions: A Resting-State EEG Study

Abstract: Altered resting-state EEG activity has been repeatedly reported in major depressive disorder (MDD), but no robust biomarkers have been identified until now. The poor consistency of EEG alterations may be due to inconsistent resting conditions; that is, the eyes-open (EO) and eyes-closed (EC) conditions. Here, we explored the effect of the EO and EC conditions on EEG biomarkers for discriminating MDD subjects and healthy control (HC) subjects. EEG data were recorded from 30 first-episode MDD and 26 HC subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In YA, Smit et al (2013) identify EOR alpha band HE maxima in the central midline consistent with other ECR and EOR studies ( Linkenkaer-Hansen, 2001 ). Moreover, other EOR studies illustrate increasing HE with age; both Nakao et al (2019) and Liu et al (2022) reported consistent ECR alpha band HE across the scalp. However, Natarajan et al (2004) report considerably lower global HE (0.29 vs ≥0.70–0.80 in other studies), and Sleimen-Malkoun et al (2015) identify a broadband global HE of 1.69, suggesting non-stationary (variation unrestricted to a singular mean/setpoint) with occipital maxima and frontal minima.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In YA, Smit et al (2013) identify EOR alpha band HE maxima in the central midline consistent with other ECR and EOR studies ( Linkenkaer-Hansen, 2001 ). Moreover, other EOR studies illustrate increasing HE with age; both Nakao et al (2019) and Liu et al (2022) reported consistent ECR alpha band HE across the scalp. However, Natarajan et al (2004) report considerably lower global HE (0.29 vs ≥0.70–0.80 in other studies), and Sleimen-Malkoun et al (2015) identify a broadband global HE of 1.69, suggesting non-stationary (variation unrestricted to a singular mean/setpoint) with occipital maxima and frontal minima.…”
Section: Resultsmentioning
confidence: 69%
“…5, Section 3.3, Auth Corr. 38 Natarajan et al, (2004) Young Adult (20.00±3.00) HE Global (1–50 Hz) 0.29±0.06 -0.42 ECR 30(15,15) Table 1 39 Liu et al, (2022) Young Adult (20−30) HE Channelwise est (Broadband)[0.5–120 Hz] EOR∼0.80–0.82 EOR0.60–0.64 ECR, EOR 26(?,?) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In YA, Smit, Linkenkaer-Hansen and de Geus (2013) identify EOR alpha band HE maxima in the central midline consistent with other ECR and EOR studies (Linkenkaer-Hansen et al ., 2001). Moreover, other EOR studies illustrate increasing HE with age; both Nakao et al ., (2019) and Liu et al ., (2022) reported consistent ECR alpha band HE across the scalp. However, Natarajan et al ., (2004) report considerably lower global HE (0.29 vs ≥0.70-0.80 in other studies), and Sleimen-Malkoun et al ., (2015) identify a broadband global HE of 1.69, suggesting non-stationary (variation unrestricted to a singular mean/setpoint) with occipital maxima and frontal minima.…”
Section: Resultsmentioning
confidence: 96%
“…Early researchers try to utilize traditional machine learning methods, i.e. support vector machine (SVM) [11]- [14], naive bayesian (NB) [15] [16], random forest (RF) [17], k-nearest neighbor (KNN) [18], logistic regression (LR) [19] [20] and decision tree (DT) [21] for MDD recognition. Among these methods, feature extraction is crucial for the accuracy improvement of MDD recognition.…”
Section: Introductionmentioning
confidence: 99%